GE_GERICHTE C/10163/2019 vom 29. Oktober 2019 - GE Cour de justice (2019)
MAINLEVÉE(LP);PÉREMPTION;MAINLEVÉE DÉFINITIVE;IMPÔT;DÉCISION DE TAXATION;TAXATION CONSÉCUTIVE À UNE PROCÉDURE | LP.80; LPGIP.36.al4; LIFD.152